Analisis Tingkat Kesukaan Konsumen, Penetapan Umur Simpan dan Analisis Kelayakan Usaha Dodol Pisang Awa - Alia Rahmi; Susi Susi; Lya Agustina (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2013)
Dodol Pisang Awa is a newly introduced local banana-based product. Several basic studies are necessary in introducing the new product to the prospective producers and consumers. Studies conducted were consumer preference level, shelf life determination and business feasibility analysis. Result showed that the taste of Dodol Pisang Awa is accepted at level 4 (hedonic scale of 1-5) followed by the aroma, overall appearance, texture, and colour. The shelf life was limited to 10 days at room temperature, transparent HDPE packaging. Feasibility analysis suggested that the business plan is feasible at profitability value of 0.77 and business efficiency of 1.77.